TEKS TUTUR LEBUR GANGSA: ANALISIS STRUKTUR DAN FUNGSI - Oka Pariatna, I Made (Humanis; Volume 16. No. 2. Agustus 2016)
This study examines the text of Tutur Lebur Gangsa. Tutur Lebur Gangsa speech laden with the teachings of the tutur, in which many advices and information that are beneficial to society (Bali). The purpose of this study was to describe the structure and functions contained in text Tutur Lebur Gangsa. Teori used in this study according to Teeuw is the structural theory, and the theory of functions according to Ratna and Damono. The method used is divided into three stages, namely at the stage of preparation of data using the methods of literary study, which supported the technical reading, translating and recording. At the level of data analysis, the method used is qualitative method supported descriptive analytic techniques, and on the presentation of data analysis using informal methods, aided by deductive and inductive techniques. The results obtained in this research that forms the structure consists of: a variety of language and style. Content structure consists of: a beginning, middle, and end. There is also a function of the oracle of Tutur Lebur Gangsa is, functions in the field of education or knowledge is knowledge of karmaphala function, the function of knowledge about the layout of housing, as well as social order regulating function Bali.
Keywords: tutur, structure, function